Influence of Extra Virgin Olive Oil on Blood Pressure and Kidney Angiotensinase Activities in Spontaneously Hypertensive Rats - Villarejo, Ana Belén; Ramírez-Sánchez, Manuel; Segarra, Ana Belén; Martínez-Cañamero, Magdalena; Prieto, Isabel (Planta Medica, 2015)
High-fat diets are associated with the development of cardiovascular diseases. The efficacy of the current strategies of treatment is still not entirely satisfactory, and new approaches are being considered. To analyze the beneficial effects of extra virgin olive oil as a major component of the Mediterranean diet, we studied systolic blood pressure and angiotensinase activities, since this enzyme is involved in the metabolism of angiotensins, in the kidney of hypertensive rats fed during 12 weeks with a diet enriched with extra virgin olive oil compared with a standard diet. As a reflex of oxidative stress, 8-isoprostanes and nitric oxide were quantified in urine. Results demonstrated a progressive increase in systolic blood pressure until the end of the feeding period in both groups. However, this increase was delayed in the extra virgin olive oil group until week six, with the systolic blood pressure being always lower in this group. Nitric oxide and 8-isoprostanes were lower in the extra virgin olive oil group. While we can deduce a higher formation of angiotensin 2–10 in the renal cortex, a higher availability of angiotensin II may be presumed in the renal medulla of animals fed an extra virgin olive oil diet than in animals fed a standard diet. Our results support the beneficial influence of extra virgin olive oil on cardiovascular function and suggest that the Mediterranean diet may be beneficial in itself but it may also be an effective tool in the treatment of hypertension.
Keywords: Olea europaea; Oleaceae; extra virgin olive oil; cardiovascular diseases; kidney; angiotensinases